Robust H∞ Mixed-sensitivity PID structural based on PSO considering input constraint - Konghuayrob, Poom; Kaitwanividvilai, Somyot (My University, 2017)
Robust control is one of the potential design methods to maintain system performance and system stability from the familial uncertainties. In addition, the limitation of performance as an input energy constraint needs to be considered to prevent the system stability degradation as well. This paper focuses on the design of H∞ mixed sensitivity based on structural PID controller for high accuracy hard disk drive servo system which examines the input saturation constraint. Particle swarm optimization (PSO) is utilized in the proposed design to maximize the system stability index called stability margin (), which consists of three norms of H∞ mixed sensitivity control. In order to confirm the effectiveness of the proposed controller, full order H∞ mixed sensitivity, the proposed PID design with considering the input constraint and trial-error tuning based PID are compared in the simulation section. It is clearly illustrated that the considering input saturation constraint is important to design the controller for sustaining the system performance. Moreover, the results confirm the robustness and performance of three controllers under the repeatable runout (RRO) disturbance. The structure of the proposed PID controller based on PSO is more simple and appropriate to apply into the actual application than the conventional H∞ mixed sensitivity full order. In addition, the results of the proposed PID controller and conventional H∞ are quite similar which can reduce the effect of RRO by 50 times and gains 50% more effective than the normal PID in terms of output error.
Keywords: Hard disk drive; H∞ robust loop shaping; Input saturation; Servo actuator; Structural PID